2020
DOI: 10.1177/2045125320973791
|View full text |Cite
|
Sign up to set email alerts
|

Early labor force exits in patients with treatment-resistant depression: an assessment of work years lost in a Danish nationwide register-based cohort study

Abstract: Background: Depression is one of the leading causes of premature workforce exit in many Western countries, but little is known about the extent to which treatment-resistance reduces number of work-years. We compared the risk of premature workforce exit among patients with treatment-resistant depression (TRD) relative to non-TRD patients and estimated work years lost (WYL) before scheduled retirement age. Methods: The study population, identified in the Danish National Prescription Registry, included all indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
(74 reference statements)
1
4
0
Order By: Relevance
“…Our study also showed a marked difference in employment as persons with TRD were associated with 36% lower odds of being employed than their comparators during 4 years follow-up after TRD. This is in line with previous studies reporting two times higher risk for disability pension, [13] and three-fold larger risk of premature workforce exit [11] and thus, showing a considerably decreased ability to attend working life. Besides high cost burden for the society and additional costs for lost tax payments and lost productivity, decreased participation in working life will also result into lifelong individual economic consequences as retirement-pension is earnings based and lower employment rate will result into a lower retirement-pension.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study also showed a marked difference in employment as persons with TRD were associated with 36% lower odds of being employed than their comparators during 4 years follow-up after TRD. This is in line with previous studies reporting two times higher risk for disability pension, [13] and three-fold larger risk of premature workforce exit [11] and thus, showing a considerably decreased ability to attend working life. Besides high cost burden for the society and additional costs for lost tax payments and lost productivity, decreased participation in working life will also result into lifelong individual economic consequences as retirement-pension is earnings based and lower employment rate will result into a lower retirement-pension.…”
Section: Discussionsupporting
confidence: 93%
“…Some definitions of TRD also include psychotherapy but detailed data on psychotherapy is lacking from many data sources and thus, cannot be included. TRD has been associated with multiple adverse outcomes as compared to regular major depressive disorder, including higher risk of suicides, [7] all-cause mortality, [8,9] substance use disorders, [10] early labor force exit, [11] and lower quality of life and greater functional and work impairment [12]. Higher risk of disability pension [11,13] and more frequent healthcare resource utilization in TRD [14][15][16][17](Brenner et.…”
Section: Introductionmentioning
confidence: 99%
“…Depressive symptoms may increase upon retiring, as distinct from increasing the probability of early retirement (Segel-Karpas et al 2018a ). A clinical diagnosis of treatment-resistant depression has been associated with a three-fold increased risk of premature workforce exit, with an average of six years of work lost (Bang Madsen et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment-resistant depression (TRD) is often defined as a patient's failure to respond to at least two consecutive antidepressant treatments in a single depressive episode, taken at adequate doses for an adequate length of time [5], though no consensus of adequacy of dose and duration exists [6]. It is a complex condition associated with comorbidities [7], higher risk of hospitalization and longer admission [8], increased suicidality and self-harm [9][10][11], increased risk of premature workforce exit [12], reduced quality of life, and poorer prognosis [13,14] compared with non-TRD MDD patients. A recent Danish nation-wide cohort study found that 15.8% of MDD patients developed TRD within 12 months of first hospital contact for major depression, corresponding to an incidence of 187.7 (185.7; 189.9) per 1,000 person-years [15].…”
Section: Introductionmentioning
confidence: 99%